EFL teachers' reflective practice, job satisfaction, and school context variables: Exploring possible relationships. Issue 1 (20th June 2019) - Aliakbari, Mohammad; Khany, Reza; Adibpour, Maryam
Abstract : Concentrating on job satisfaction and five school context variables—teacher autonomy, collegial support, time pressure, student demotivation, and student discipline problems—this study explored the interplay of these variables with reflective teaching and their relative contributions to prediction of teacher reflection. Data were collected from 181 Iranian high school teachers. The results of correlational analysis revealed that all independent variables significantly correlated with teacher reflection. Strong positive relationships were found between job satisfaction, teacher autonomy, and reflective practice. Time pressure, student demotivation, and student discipline problems strongly and negatively correlated with reflective teaching. Moreover, a small positive correlation was found between supportive social climate and reflective practice. The results of multiple regression indicated that, except for supportive social climate, all independent variables made statistically significant contributions to prediction of teacher reflection. Considering the shaping influence of educational policies on correlates of teacher reflection, the findings reflect the necessity of reform in policy makers' approach. Implying English as a foreign language (EFL) teachers' ignorance of collaborative dimensions of reflective practice, the results call attention to the importance of preservice and in‐service teacher educational programs and the necessity of effective monitoring systems supervising public school teachers.